Experiments with 'SPRITE' 12 ps facility - Tallents, G; Key, M; Norreys, P; Jacoby, J; Kodama, R; Tragin, N; Baldis, H; Dunn, J; Brown, D (Publ by Int Soc for Optical Engineering, 1991)
Lateral and axial thermal energy transport in laser-plasma interactions has been studied using a short (12 psec) pre-pulse free KrF pumped Raman laser pulse (λ = 268 nm) of low beam divergence. A new method of producing narrow line foci using random phase plates was employed to study the plasma conditions required to generate high gain, short wavelength recombination X-ray lasers. In addition, the laser energy was focused into a small focal spot (8 μm) for higher intensity (1-2 × 1017 cm-2) interaction studies.